2018
DOI: 10.1016/j.cell.2018.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA Compaction in Stationary-Phase Bacteria Does Not Affect Transcription

Abstract: In stationary-phase Escherichia coli, Dps (DNA-binding protein from starved cells) is the most abundant protein component of the nucleoid. Dps compacts DNA into a dense complex and protects it from damage. Dps has also been proposed to act as a global regulator of transcription. Here, we directly examine the impact of Dps-induced compaction of DNA on the activity of RNA polymerase (RNAP). Strikingly, deleting the dps gene decompacted the nucleoid but did not significantly alter the transcriptome and only mildl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 72 publications
6
108
0
1
Order By: Relevance
“…While BR-bodies and CcmM-Rubisco condensates are currently the only bacterial biomolecular condensates whose components have been directly shown to form liquid-like droplets in physiological conditions (Al-Husini et al, 2018; Wang et al, 2019), the cell division protein FtsZ and its inhibitor SlmA were shown to form condensates upon addition of crowding reagents (Monterroso et al, 2019). In addition, other bacterial proteins such as the polar protein scaffold PopZ (Lasker et al, 2018; Zhao et al, 2018) and the nucleoid associated protein DPS (Janissen et al, 2018) have been shown to act as selectively permeable scaffolds, yet biomolecular condensation has not been directly observed.…”
Section: Discussionmentioning
confidence: 99%
“…While BR-bodies and CcmM-Rubisco condensates are currently the only bacterial biomolecular condensates whose components have been directly shown to form liquid-like droplets in physiological conditions (Al-Husini et al, 2018; Wang et al, 2019), the cell division protein FtsZ and its inhibitor SlmA were shown to form condensates upon addition of crowding reagents (Monterroso et al, 2019). In addition, other bacterial proteins such as the polar protein scaffold PopZ (Lasker et al, 2018; Zhao et al, 2018) and the nucleoid associated protein DPS (Janissen et al, 2018) have been shown to act as selectively permeable scaffolds, yet biomolecular condensation has not been directly observed.…”
Section: Discussionmentioning
confidence: 99%
“…All individual DWT distributions qualitatively exhibit the same features, a peak at short time scales (~ 400 ms for the provided example) and a tail of gradually decreasing probability for DWT >1 s. While the peak reflects the pause-free elongation, the tail originates from pauses. 54,55 We observe a significant variation between individual DWT distributions, particularly in the occurrence of extremely long-lived pauses. While for the majority of the analyzed RNAp trajectories the longest observed pauses lie well below 450 s (Figure 1D, red), a small fraction of trajectories (~ 10%) show single pauses extending to few thousand seconds (Figure 1D, blue).…”
Section: Rnap Transcription Dynamics Exhibit Notable Heterogeneitymentioning
confidence: 85%
“…In agreement with previous studies, the RNAp trajectories ( Figure 1B) exhibit periods of apparently constant translocation velocities, punctuated by pauses of different duration and position. 32,54 To capture the probabilistic nature of RNAp translocation and stochastic pausing, we constructed dwell-time (DWT) distributions from DWTs obtained for all trajectories. 55 These DWTs were extracted from individual trajectories ( Figure 1C) by measuring the time needed for each individual RNAp to successively transcribe a fixed number of nucleotides (Methods M3).…”
Section: Rnap Transcription Dynamics Exhibit Notable Heterogeneitymentioning
confidence: 99%
“…The dramatic changes in the DNA topology induced by Dps have raised a question as to how DNA can be accessible to transcription and other processes connected with DNA metabolism in stationary phase cells. Recently, Janissen and colleagues [79] have demonstrated that RNA polymerase can freely enter and diffuse inside the Dps complexes, whereas other proteins such as restriction enzymes are blocked from accessing the DNA. The authors of this study have suggested that in such way Dps ensures transcriptional response to the encountered stress while protecting the genome from damage.…”
Section: A Role Of Naps In Mutagenesis and Recombination Processesmentioning
confidence: 99%